2004
DOI: 10.5713/ajas.2004.374
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Plant Extract Supplementation on Performance and Blood Characteristics in Weaned Pigs

Abstract: One hundred and twenty crossbred pigs [(Duroc×Yorkshire)×Landrace] were used to determine the effects of plant extract (PE) supplementation on performance and blood characteristics in weaned pigs fed a corn-dried whey-SBM based diet. Treatments were 1) NC (antibiotic free basal diet), 2) PC (NC diet+100 ppm apramycin and 100 ppm oxytetracycline), 3) PE 0.1 (NC diet+0.1% plant extract), 4) PE 0.2 (NC diet+0.2% plant extract) and 5) PE+AB (PC diet+0.1% plant extract). Through the entire experimental period, ADG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
7
20
0
Order By: Relevance
“…Results suggest that EO improved the ADG and G/F during the grower phase, which was in agreement with Hong et al (2004), who reported that the ADG of pigs fed 2 or 3% botanical extracts were significantly improved when compared to those of pigs fed diets without botanical supplementation. However, such an effect was not observed in the residual period in the present study, which may have been due to the more developed digestive system, improved immunity, and increased resistance to intestinal disorders as pig become older (Nousiainen and Setala, 1993).…”
Section: Effects Of Essential Oilssupporting
confidence: 91%
See 1 more Smart Citation
“…Results suggest that EO improved the ADG and G/F during the grower phase, which was in agreement with Hong et al (2004), who reported that the ADG of pigs fed 2 or 3% botanical extracts were significantly improved when compared to those of pigs fed diets without botanical supplementation. However, such an effect was not observed in the residual period in the present study, which may have been due to the more developed digestive system, improved immunity, and increased resistance to intestinal disorders as pig become older (Nousiainen and Setala, 1993).…”
Section: Effects Of Essential Oilssupporting
confidence: 91%
“…Accordingly, many studies have been conducted to identify alternatives to antibiotics as growth promoters in the animal industry (Hong et al, 2004;Cho et al, 2006). One such alternative, essential oils (EO), which are also referred as volatile or ethereal oils, are aromatic oily liquids acquired from plant materials (flowers, buds, seed, leaves, twigs, bark, herbs, woods, fruits, and roots) that are generally recognized as safe by the Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of essential oils also improves growth performance (Simonson, 2004;Windisch et al ., 2008;Dalkiliç and Güler, 2009) and decreases fecal scores (Hong et al ., 2004) because of its antimicrobial effects (Dorman and Deans, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, phytogenic feed additives have been wildly used as an alternative to antibiotics because of their plant-derived property and growth-promoting effects (Hong et al 2004;Wang et al 2007;Wang et al 2008;Windisch et al 2008;Jang et al 2010;Ao et al 2011). Valchev et al (2009) demonstrated that herbal extracts (150 mg/kg) in pig diet could increase growth performance, feed efficiency, and immune-related blood characteristics.…”
Section: Introductionmentioning
confidence: 99%